Karikatur Covid-19 Dalam Media Daring Tempo dan Kompas: Kajian Semiotika - Mardi Ardi Amin, Arlyanti Dwi Putri Muhammad Hasyim (Universitas Sam Ratulangi, 2021)
This study aims to describe the Covid-19 handling policies in the caricatures 0f @tempodotco and @hariankompas and to determine the meaning depicted in the caricatures as well as public reactions to government policies. The data used are sourced from caricatures contained in the Instagram accounts @tempodotco and @hariankompas regarding government policies in handling covid-19 published in March-December 2020. The data found are divided into 7 sub-themes, namely about elections, social assistance, new normal, work from home or studying from home, PSBB or social distancing, government opinion, and the prohibition on going home. The author concludes that the results of this study are divided into two. The first is the depiction that appears about government policies and the reactions of the people that are depicted. The descriptions that emerge about government policies are divided into 4. (1) The determination of government policies is described as less strict on the implementation of health protocols. (2) Government policies that have been implemented are described as complying with the process but not providing solutions for the impacts that arise. (3) Opinions expressed by several government officials seem to underestimate COVID-19. (4) Misuse of social assistance for campaign purposes. The depiction emerges from the public's reaction to government policies. Divided into 3. (1) The community is described as not complying with government regulations properly. (2) Employees or students cannot perform their duties efficiently. (3) Human is depicted as a bird in a cage.